Characterization of uncertainty in maximum tidal elevation near Bangladesh coastline due to uncertain sea level rise - Sifat Sarwar; Alistair G. L. Borthwick (Journal of Flood Risk Management, 2023)
Abstract The Ganges‐Brahmaputra‐Meghna delta is vulnerable to sea level rise from global warming. Based on sea level rise predictions for the year 2100 given in the 6th Assessment Report by the Intergovernmental Panel on Climate Change (IPCC), we examine the effect of uncertainty in sea level rise on maximum tidal elevation statistics at several locations along the Bangladesh coastline using a discretized derived distribution approach. For five IPCC scenarios, the standard deviation in maximum tidal elevation including sea level rise is predicted to increase by between 3% and 61% at three different locations for a 41% increase in the standard deviation of mean sea level rise. By excluding the linear effect of sea level rise, the increase in the standard deviation of maximum tidal elevation is found to vary spatially from 2% to 68% with a 41% increase in the standard deviation of sea level rise.